Expression of growing and slaughtering qualities of Swedish Landrace pigs according to sex - Šperanda, Marcela; Senčić, Đuro; Uremović, Marija; Antunović, Boris; Antunović, Zvonko (Acta Agraria Kaposváriensis, 1999)
Better slaughtering and fattening results have induced more frequent fattening of young uncastrated boars. While fattening boars, the problem of unpleasant odour from the boar meet, which is caused by endosteron, scatol and other testicular hormones, often occurs. There are some differences between genetic bases of swine in extracting of these hormones. Therefore, the cam of this paper was to pay more attention on legitimacy of slaughtering Swedish Landrace uncastrated boars. The experiment was carried out on a group of uncastrated boars and a group of uncastrated gilts. The groups were composed of 15 accidentally chosen pigs per group from 15 different litters (one male and one female pig from each litter). The experimental fattening lasted for 95 days (from 30 to 90 kg of body weight) and the pigs were fed ad libitum. The boars had significantly higher daily growth rate (660g vs. 640g, P0.05). The pork sides were dissected according to the method by Weniger et al. (1963).Keywords: sex; boars; gilts; growth rate; slaughtering quality
Keywords: sex; boars; gilts; growth rate; slaughtering quality